2012
DOI: 10.1371/journal.pone.0035178
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Death-1 and Its Ligand Are Novel Immunotolerant Molecules Expressed on Leukemic B Cells in Chronic Lymphocytic Leukemia

Abstract: Programmed death-1 (PD-1) is an immunoreceptor predominantly expressed on exhausted T cells, which through an interaction with its ligand (PD-L1), controls peripheral tolerance by limiting effector functions of T lymphocytes. qRT-PCR for PD-1, PD-L1 and their splicing forms as well as flow cytometric assessment of surface expression was performed in a cohort of 58 chronic lymphocytic leukemia (CLL) patients. In functional studies, we assessed the influence of the proliferative response of leukemic B-cells indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 41 publications
5
46
1
2
Order By: Relevance
“…39 Expression of PD-1 on the neoplastic counterpart was reported in a limited number of diffuse large B-cell lymphomas and in a more significant number of small lymphocytic lymphomas. A fraction of circulating CLL cells is also reported as PD-1 + (see Grzywnowicz et al 17 and Li et al 18 and confirmed in this work) even if the prognostic and functional implications remain unknown.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…39 Expression of PD-1 on the neoplastic counterpart was reported in a limited number of diffuse large B-cell lymphomas and in a more significant number of small lymphocytic lymphomas. A fraction of circulating CLL cells is also reported as PD-1 + (see Grzywnowicz et al 17 and Li et al 18 and confirmed in this work) even if the prognostic and functional implications remain unknown.…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, a fraction of CLL lymphocytes, identified on the basis of CD19/CD5 surface expression, was PD-1 + ( Figure 1C), confirming previous observations. 17 On the contrary, circulating B lymphocytes from controls were mostly PD-1 -( Figure 1C). The PD-L1 ligand was found to be restricted to B lymphocytes in CLL and control samples; however, CLL B lymphocytes expressed significantly more PD-L1 when compared to B lymphocytes cells from controls ( Figure 1D).…”
Section: Cd4mentioning
confidence: 93%
“…34 Similar expression patterns were described in flow-cytometry-based studies. 60,61 In contrast, the majority of examined SLL/CLL full tissue sections collected from three different institutions (n=58) were PD-1-in another study, 40 similar to earlier findings of a lack of PD-1 expression on CLL cells. 33 …”
Section: Pd-l1/pd-1 Expression On Tumor Cellssupporting
confidence: 80%
“…34,60,61 Using an extremes of survival approach and a limited number of patient samples, we found significant-…”
Section: Prognostic Relevance Of Pd-l1/ Pd-1 Expression In Cllmentioning
confidence: 99%
See 1 more Smart Citation